Transcriptomic and Phenomic Investigations Reveal Elements in Biofilm Repression and Formation in the Cyanobacterium Synechococcus elongatus PCC 7942 - Simkovsky, Ryan; Parnasa, Rami; Wang, Jingtong; Nagar, Elad; Zecharia, Eli; Suban, Shiran; Yegorov, Yevgeni; Veltman, Boris; Sendersky, Eleonora; Schwarz, Rakefet; Golden, Susan S. (Frontiers in Microbiology, 2022)
Biofilm formation by photosynthetic organisms is a complex behavior that serves multiple functions in the environment. Biofilm formation in the unicellular cyanobacterium Synechococcus elongatus PCC 7942 is regulated in part by a set of small secreted proteins that promotes biofilm formation and a self-suppression mechanism that prevents their expression. Little is known about the regulatory and structural components of the biofilms in PCC 7942, or response to the suppressor signal(s). We performed transcriptomics (RNA-Seq) and phenomics (RB-TnSeq) screens that identified four genes involved in biofilm formation and regulation, more than 25 additional candidates that may impact biofilm formation, and revealed the transcriptomic adaptation to the biofilm state. In so doing, we compared the effectiveness of these two approaches for gene discovery.